The broad autism phenotype - Rotatori, Anthony F. (Bingley, U.K. : Emerald, 2015)
This proposed volume will provide in-depth coverage about a construct known as the broad autism phenotype (BAP). The BAP encompasses biological, cognitive, emotional, behavioral, and interpersonal characteristics resembling those found on the autism spectrum, although more subtle than what is evident among individuals who meet formal criteria for an autism spectrum diagnosis. Initially identified in 1994, the BAP has been receiving increased attention due to the recognition of autism as a spectrum of disorders that vary in symptoms and severity.
Recognition of the broad autism phenotype -- Identification and assessment of the broad autism phenotype -- Genetic aspects of the broad autism phenotype -- Other biological aspects of the broad autism phenotype -- Cognitive functioning in the broad autism phenotype.
Print version record
Keywords: Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Autism; Phenotype